Semiotika dalam Album Manusia dan Monokrom Karya Tulus dan Implikasinya terhadap Pembelajaran Teks Puisi di Kelas X SMA - Eva Febriyanti; Erwan Kustriyono (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language and semiotics have a close relationship and are interrelated. Language is a system of signs that humans use to communicate, while semiotics is the science that studies signs. Semiotics is a science that studies signs. This paper aims to describe the semiotic studies contained in the lyrics of the albums